2012
DOI: 10.1891/1058-1243.21.4.229
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth Education and Obstetric Interventions Among Low-Risk Canadian Women: Is There a Connection?

Abstract: The objective of this study was to examine the associations between attendance at childbirth education classes and maternal characteristics (age, income, educational level, single parent status), maternal psychological states (fear of birth, anxiety), rates of obstetric interventions, and breastfeeding initiation. Between women's 35th and 39th weeks of gestation, we collected survey data about their childbirth fear, anxiety, attendance at childbirth education classes, choice of health-care provider, and expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 24 publications
3
24
1
1
Order By: Relevance
“…The British study indicated that attendance at childbirth education classes was related to a significantly lower caesarean section rate, among multiparous women who attended in childbirth classes attempted more than twice as many vaginal birth after caesarean. 4 Women in control group in this study, the majority of women who stated that women's fear of childbirth related to labour pain, emergency cesarean, fear of death, baby with disabled and malformation, loss of control, perineal and vaginal tears and unfriendly staff maternity hospital. In Finland study indicated that causes of fear were emergency cesarean section, child's and mother's well-being, childbirth and family life and 78% pregnant women stated fears related to pregnancy and childbirth.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The British study indicated that attendance at childbirth education classes was related to a significantly lower caesarean section rate, among multiparous women who attended in childbirth classes attempted more than twice as many vaginal birth after caesarean. 4 Women in control group in this study, the majority of women who stated that women's fear of childbirth related to labour pain, emergency cesarean, fear of death, baby with disabled and malformation, loss of control, perineal and vaginal tears and unfriendly staff maternity hospital. In Finland study indicated that causes of fear were emergency cesarean section, child's and mother's well-being, childbirth and family life and 78% pregnant women stated fears related to pregnancy and childbirth.…”
Section: Discussionmentioning
confidence: 90%
“…In other experimental studies on the same topic, women who attended pregnant education classes were found to have less fear of childbirth. 4,6,10 In Finland study reported that pregnant women in antenatal education group had less fear of childbirth than those in the control group. 9 Fabian and colleagues reported that the majority of women (74%) found antenatal education classes helpful in preparing for childbirth and early parenthood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations